Infrastructure and regional cooperation - Haruhiko Kuroda; Masahiro Kawai; Rita Nangia (Asian Development Bank Institute (ADBI), 2007)
Continuing Asia's extraordinary transformation will require increasing attention on regional connectivity and logistic systems. The article focuses on the role of cross-border infrastructure in the process of regional integration in developing Asia. Given that most cross-border infrastructure projects are very complex, actions will need to be taken by various stakeholders-Asian governments, the private sector, civil society organizations, and multilateral institutions-in connecting Asia.
Keywords: O18; L9; N7; 330; Außenwirtschaft; Direktinvestition; Infrastrukturinvestition; Entwicklung; Asien